The Intestinal Flora at Kasai Procedure in Children with Biliary Atresia Appears Not to Affect Postoperative Cholangitis - Madadi-Sanjani, Omid; Schukfeh, Nagoud; Uecker, Marie; Eckmann, Stefanie; Dingemann, Jens; Ure, Benno M.; Petersen, Claus; Kuebler, Joachim F. (European Journal of Pediatric Surgery, 2020)
Introduction Evidence supports long-term oral antibiotic prophylaxis to prevent cholangitis after Kasai procedure. Data regarding perioperative intravenous prophylaxis are lacking. Ascending pathogens from the intestine are made responsible for recurrent cholangitis. Therefore, we analyzed the flora in the upper jejunum during the Kasai procedure and their potential impact on postoperative cholangitis.Materials and Methods In 26 patients, swabs were taken at the bowel prepared for the Roux-en-Y-loop. Our postoperative protocol includes intravenous third-generation cephalosporins for 2 weeks and rectal steroids starting at day 4. Cholangitis was defined as the postoperative reappearance of acholic stools or increase of serum bilirubin in combination with fevers or increase of inflammatory parameters. In this scenario, Tazocin was administered for another 2 weeks.Results Swabs remained sterile in nine patients (34.6%). In 17 patients (65.4%), gram-positive and gram-negative pathogens were identified; all belonging to physiological intestinal flora. A total of 96.2% pathogens were covered by the antibiotic prophylaxis. The cholangitis incidence was 55.6% in the sterile cohort, and 23.5% in the gram-positive and gram-negative cohort (p = 0.06). In the cholangitis cohort, no significant differences were detected for the age at Kasai and the pre- and postoperative total bilirubin.Conclusion We found that our antibiotic regiment covered bacteria in the upper gastrointestinal (GI) tract in the majority of our patients at the time of Kasai. Nonetheless, a significant proportion of patients developed signs of cholangitis. There was no higher rate of cholangitis in patients with resistant bacteria. Thus, our data do not support the hypothesis of extended postoperative intravenous antibiotics to prevent ascending cholangitis.
Keywords: biliary atresia; cholangitis; intestinal flora; antibiotics